New crops, local soils and urbanization: Clover, potatoes and the growth of Danish market towns,1672-1901 - Torben Dall Schmidt; Peter Sandholt Jensen; Amber Naz (European Historical Economics Society (EHES), 2014)
This research evaluates the impact of the introduction of clover and potatoes on urbanization using a panel of Danish market towns from 1672 to 1901. We find evidence that both clover and potatoes contributed to urbanization using a difference-in-difference type estimation strategy which exploits that the breakthrough of clover and potatoes should have differential local effects because of soil suitability. To take into account the endogeneity of clover adoption, we instrument by suitability for growing alfalfa, which like clover is a legume. Importantly, alfalfa did not have its breakthrough in the period studied. Our IV estimates suggest that clover accounted for about 8 percent of market town population growth between 1672 and 1901, whereas roughly 6 percent can be attributed to potatoes. The analysis also indicates that the potato had its breakthrough later in Denmark than in many other countries as suggested by the historical narrative.
Keywords: N1; N9; O1; O4; R11; 330; clover; potatoes; agricultural productivity; urbanization